Japanese subgroup analysis of EV‐301: An open‐label, randomized phase 3 study to evaluate enfortumab vedotin versus chemotherapy in subjects with previously treated locally advanced or metastatic urothelial carcinoma - Matsubara, Nobuaki; Yonese, Junji; Kojima, Takahiro; Azuma, Haruhito; Matsumoto, Hiroaki; Powles, Thomas; Rosenberg, Jonathan E.; Petrylak, Daniel P.; Matsangou, Maria; Wu, Chunzhang; Campbell, Mary; Yamashiro, Mayumi (Cancer medicine (Malden, MA), 2023)
Background Enfortumab vedotin (EV) is an antibody‐drug conjugate showing significant overall survival (OS) benefit versus chemotherapy for patients with previously treated locally advanced or metastatic urothelial carcinoma (la/mUC) in EV‐301. This subgroup analysis was conducted to further analyze the efficacy and safety in a Japanese population. Methods In the open‐label, phase 3 EV‐301 trial, patients with la/mUC were randomized 1:1 to EV 1.25 mg/kg on Days 1, 8, and 15 for 28‐day cycles or investigator‐preselected standard chemotherapy (SC; docetaxel or paclitaxel for patients in Japan) on Day 1 of each 21‐day cycle. Primary endpoint was OS and secondary efficacy endpoints included progression‐free survival (PFS) and overall response rate (ORR). Safety/tolerability was also evaluated. Results As of the July 15, 2020 cut‐off date for the interim analysis, the Japanese subgroup included 86 patients (EV: n = 36; SC: n = 50). Median OS was 15.18 months for EV and 10.55 months for SC (HR: 0.437 [95% CI: 0.209, 0.914]). Median PFS was 6.47 months for EV and 5.39 months for SC (HR: 0.464 [95% CI: 0.258, 0.835]). Confirmed ORR was 34.4% for EV and 21.3% for SC. A higher proportion of patients receiving SC versus EV had treatment‐related adverse events (TRAEs; 97.9% vs. 91.7%, respectively), including grade ≥ 3 TRAEs (75.0% vs. 63.9%). Conclusions This subgroup analysis confirmed that EV, with consistent efficacy and safety/tolerability in the EV‐301 Japanese subgroup and overall study population, represents an important treatment option for previously treated patients with la/mUC. In the global, open‐label, phase 3 EV‐301 trial, enfortumab vedotin (EV) demonstrated clinically significant overall survival (OS) benefit compared with standard chemotherapy in patients with previously treated locally advanced or metastatic urothelial carcinoma. This subgroup analysis of EV‐301 Japanese patients confirmed that EV demonstrated an OS benefit and no new safety signals identified in the Japanese subpopulation, consistent with the efficacy and safety/tolerability in the EV‐301 overall study population.